Russian-language repository of the open clinical data “SibMED Data Clinical Repository” - E. S. Kulikov; O. S. Fedorova; I. V. Tolmachev; U. V. Ryazantseva; D. A. Vrazhnov; A. V. Gubanov; S. V. Nesterovich; A. A. Shmyrina (Бюллетень сибирской медицины, 2023)
The global digitalization has become one of the most significant challenges in the field of medicine and healthcare. The rapid development of digital technologies determines the growing demand for constant access to big data in real time Their use is in need for research and technological projects in the sphere of artificial intelligence technologies development. Siberian State Medical University developed the first Russian-language repository of clinical data “SibMed Data Clinical Repository” (https://dataset.ssmu.ru/). The article describes the structure, functions of the repository, and perspectives of its use.